A study of student participation and nonparticipation in prelecture electronic surveys. (12th December 2012) - Tong, Vincent C. H.; Chow, Danny S. L.
Abstract: Student nonparticipation in electronic surveys represents a challenge to educators as it may impact significantly on the implementation or evaluation of the associated teaching activities. We here study the student evaluation of a pedagogical project consisting of prelecture online polling followed by linked revision lectures. This investigation involves studying the responses from 43 undergraduate students following a course in accounting at a British university. With regard to the students' views on the use of prelecture polling, our study shows that there are no statistically significant differences between those who did not participate in the online polling and those who did. Both groups of students were generally positive about the use of (1) polling results in structuring the revision lecture, (2) online survey in helping them prepare for the examination and (3) online polling as a teaching platform in other courses. Our findings therefore suggest that prelecture electronic surveys can help engage students with follow‐up lectures, including those who did not participate in the prelecture survey.